Selective Control : The Political Economy of Censorship - Corduneanu-Huci, Cristina; Hamilton, Alexander (World Bank, Washington, DC, 2018)
In recent years, alongside democratic backsliding and security threats, censorship is increasingly used by governments and other societal actors to control the media. Who is likely to be affected by censorship and why? Does censorship as a form of punishment coexist with or act as a substitute for reward-based forms of media capture such as market concentration or bribes? First, this argues that censors employ censorship only toward certain targets that provide information to politically consequential audiences, while allowing media that caters to elite audiences to report freely. Second, the paper hypothesizes that coercion and inducements are substitutes, with censorship being employed primarily when bribes and ownership fail to control information. To test these hypotheses, a new data set was built of 9,000 salient censorship events and their characteristics across 196 countries between 2001 and 2015. The study finds strong empirical support for the theory of media market segmentation.